2011
DOI: 10.1007/s00296-011-1959-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of CD4 enhancer gene polymorphisms with rheumatoid arthritis in Egyptian female patients

Abstract: CD4 is a candidate gene in autoimmune diseases, including rheumatoid arthritis (RA). Because the CD4 receptor is crucial for appropriate antigen responses of CD4+ T cells, changes in CD4 expression and CD4+ T-cell activity may influence tolerance or tissue destruction in autoimmune diseases and contribute to their risk. We analyzed two polymorphisms of the CD4 in 172 female Egyptian patients with RA and in 112 matched healthy control. Genotyping of CD4-11743 and CD4-10845 was determined by restriction fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The CD4 protein was confirmed to play an important role in the development of T cells and the immune response [19], and the CD4 gene was an important candidate for immune-related diseases in humans and pigs [13,20,21]. The CD4 gene interacted with the MHC gene, and both of them were rich in SNP sites [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CD4 protein was confirmed to play an important role in the development of T cells and the immune response [19], and the CD4 gene was an important candidate for immune-related diseases in humans and pigs [13,20,21]. The CD4 gene interacted with the MHC gene, and both of them were rich in SNP sites [22].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, three SNPs in the promoter region of the CD4 gene were related to type 1 diabetes mellitus [12]. A trait-association study indicated the relationship of two SNPs in the enhancer regions to the severity of rheumatoid arthritis [13]. Furthermore, one C to T substitution at nucleotide position 868 of the CD4 gene was related to HIV-1 acquisition and disease progression in Kenyans [14][15][16].…”
mentioning
confidence: 99%
“…Genetic mutations responsible for phenotypic difference are the most effective choice of markers assisted selection in dairy cattle breeding programs (Dekkers & Hospital 2002). Different studies have reported that the important functional role of enhancer and flanking region in transcription initiation and regulation (Dekkers & Hospital 2002;Hussein et al 2012;Lee et al 2010;Lomvardas et al 2006). Thus, genetic variation in the flanking regions of a gene can significantly influence a phenotypic trait (Bulger & Groudin 2011;Zhang et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Most human autoimmune diseases require CD4 T cells for their development including Type 1 diabetes mellitus(T1DM) [68,69], vitiligo [8], and RA which are considered one of the most common autoimmune diseases [70]. RA is assumed to be an autoimmune disease, based on the presence of auto antibodies in the serum and remarkable lymphocyte infiltration into the synovium [65].…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence to support the involvement of lymphocytes in the pathogenesis of RA, including the presence of CD4+ T cells in RA synovium. The CD4 receptor is glycoprotein expressed on the surface of helper T cells colocalizes with the T-cell receptor (TCR) and major histocompatibility complex (MHC) class II molecules and interacts with the non-antigen-binding regions on the MHC class II molecule in antigen recognition [7,8].Theoretically, any malfunction of the CD4 receptor could potentially allow for improper activation and proliferation of CD4+ T cells [9]. Inhibition of CD4-MHC class II interaction severely impairs the response of T cells to antigen exposure, and low CD4 cell surface expression on the lymphocytes results in impaired TCR response to lowlevel antigenic stimulation [10].…”
Section: Introductionmentioning
confidence: 99%